eNOS-dependent S-nitrosylation of the NF-κB subunit p65 has neuroprotective effects - Caviedes, Ariel (Cell Death Dis, 2021)
Cell death by glutamate excitotoxicity, mediated by N-methyl-d-aspartate (NMDA) receptors, negatively impacts brain function, including but not limited to hippocampal neurons. The NF-κB transcription factor (composed mainly of p65/p50 subunits) contributes to neuronal death in excitotoxicity, while its inhibition should improve cell survival. Using the biotin switch method, subcellular fractionation, immunofluorescence, and luciferase reporter assays, we found that NMDA-stimulated NF-κB activity selectively in hippocampal neurons, while endothelial nitric oxide synthase (eNOS), an enzyme expressed in neurons, is involved in the S-nitrosylation of p65 and consequent NF-κB inhibition in cerebrocortical, i.e., resistant neurons. The S-nitro proteomes of cortical and hippocampal neurons revealed that different biological processes are regulated by S-nitrosylation in susceptible and resistant neurons, bringing to light that protein S-nitrosylation is a ubiquitous post-translational modification, able to influence a variety of biological processes including the homeostatic inhibition of the NF-κB transcriptional activity in cortical neurons exposed to NMDA receptor overstimulation.